Delays in Seeking Medical Services in Elderly Patients With Senile Cataract - Xiang, Yifan; Jiang, Haofeng; Zhao, Lanqin; Liu, Qiong; Lin, Haotian (Frontiers in Psychology, 2022)
Delay seeking medical services is common in older populations, leading to disease progression and life difficulty. This study aims to assess the prevalence of delay in medical visits and treatment, and define associated effects and factors in patients with senile cataracts, which may help obtain a better understanding of late-life psychopathology and provide the basis for interventions. Patients aged more than 60 years old were recruited to Zhongshan Ophthalmic Center (ZOC). All participants were diagnosed with binocular senile cataracts and decided to have primary surgery in ZOC. The descriptive statistic accessed the distributions of the popularity of delaying outpatient visits and treatment, the degrees of visual impairment, the influences on quality of life, and the reasons for delaying treatment among participants. Factors associated with the perceptions of cataract treatment were accessed using a binary logistic regression model. A total of four hundred senile patient aged from 60 to 94 years old were enrolled. At the time of diagnosis, 82 (20.5%) participants had low vision with monocular acuity of both eyes below 0.05. All participants have felt normal life was affected and 64 (16%) participants felt life was affected severely. Only 17 (4.25%) participants sought medical services after feeling vision loss, and 294 (73.50%) participants had felt vision loss since a year ago before seeking medical help. Nearly three-quarters of the participants (298) postponed their surgeries, with 229 (57.25%) patients delaying it for more than 12 months. There were 147 (36.75%) participants delaying surgery on account of no knowledge about it and 114 (28.50%) participants delaying surgery because of fear. A considerable number of older individuals with cataracts postpone outpatient visits and surgical procedures, which substantially impairs their quality of life. Increasing medical service propaganda about cataracts and other common diseases in older populations would help improve perceptions of diseases and decrease medical delays. The public must draw more attentions to the healthy and medical status of the older ocular patients.